A PENHORA DO BEM DE FAMÍLIA DO FIADOR DA LOCAÇÃO: UMA ANÁLISE À LUZ DA PRINCIPIOLOGIA JURÍDICA - Strasburger, Florian (2007)
The objective of this research is the analyse of the polemic question to stand surety within the home rent contracts, new perspectives and interpretations has been created with EC 26/2000. The discussion, is the rising of the status of home to a law level of fundamental rights, with the legal possibility homestead attachment. That way is created a normative conflict between the laws 8.009/90 and 8.245/91. This fact of a new vision of the law challenges the jurisprudence to interpretate the question. Analising each of that two dispositions, the social impact, the characteristic of the financial institutions, the concept of the state and the two paradigmatics agreements of the highest level of brazilian court, inspired by hermeneutics fountains, is to create a proposal from the juridical principle theory, trying that way to find out a proposal of solution to the conflicts linked to an axiologic-normative concept of Law.